2017
DOI: 10.1080/07315724.2017.1347908
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Fatty Acids, Desaturase and Elongase, and Insulin Resistance in Children

Abstract: There was no relationship between these lipid markers and adiposity in this population; however, there were correlations with HOMA-IR. Regardless of adiposity, there may be underlying changes in fatty acid and lipid metabolism associated with the development of metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
7
2
Order By: Relevance
“…In a prevalence study, IR was positive in 28.9% of females and 25.1% of males [15]. In one study, on average, 25% of overweight individuals had insulin resistance; however, in the present study, 52.5% of the total study sample tested positive for IR although our patients had normal body weight [16]. In contrast to previous studies, 73.7% of our patients tested positive for insulin resistance.…”
Section: Discussioncontrasting
confidence: 92%
“…In a prevalence study, IR was positive in 28.9% of females and 25.1% of males [15]. In one study, on average, 25% of overweight individuals had insulin resistance; however, in the present study, 52.5% of the total study sample tested positive for IR although our patients had normal body weight [16]. In contrast to previous studies, 73.7% of our patients tested positive for insulin resistance.…”
Section: Discussioncontrasting
confidence: 92%
“…In one study, on average, 25% of overweight individuals had insulin resistance; however, in the present study, 52.5% of the total study sample tested positive for insulin resistance although our patients had normal body weight [23]. As reported in literature, some children with normal body weight show a higher-than-average HOMA value and the underlying cause of this is not clear.…”
contrasting
confidence: 73%
“…SCD-1 was supposed to protect against the harmful effects of saturated FA accumulation in tissues and bloodstream by metabolizing them into monounsaturated FA [24]. Anyhow, animal models showed an unfavorable association with cardiovascular risk factors [25,26] Although the role of SCD-1 in humans is not completely understood, several studies reported its unfavorable association with cardiometabolic profile, in particular with BP [27], obesity [28] and insulin sensitivity [29], even in children [30]. Also, our results show higher SCD-16 activity in the excess-weight group and direct associations among the desaturase activity and several CV risk factors, which were stronger in overweight/obese than in normal-weight children.…”
Section: Discussionmentioning
confidence: 99%